Cover Feature: Metal‐Free N‐Doped Carbon Catalyst Derived from Chitosan for Aqueous Formic Acid‐Mediated Selective Reductive Formylation of Quinoline and Nitroarenes (ChemSusChem 23/2022). Issue 23 (18th November 2022) - Chauhan, Arzoo; Banerjee, Arghya; Kar, Ashish Kumar; Srivastava, Rajendra
Abstract : The Cover Feature shows a metal‐free, N‐doped carbon‐mediated sustainable catalytic route for selective reductive formylation of quinoline to N ‐formyl‐tetrahydroquinoline and nitroarenes to N ‐formyl anilides via aqueous formic acid mediated catalytic transformation. The boat (built with chitosan derived from crabs) represents the chitosan‐derived N‐doped carbon catalyst sailing in the water containing formic acid. More information can be found in the Research Article by A. Chauhan et al .